HW 7 - 30 E(X-Y)2 = E(X-Y)2]=E[cfw(X(Y)2]= E(X)2-2(X(Y(Y)2...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
30. E[(X-Y) 2 ] = E[(X-μ+μ-Y) 2 ]=E[{(X- μ)-(Y- μ)} 2 ]= E[(X- μ) 2 -2(X- μ)(Y- μ)+(Y- μ) 2 ] = E[(X- μ) 2 ]-2E[(X- μ)(Y- μ)]+E[(Y- μ)
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
Background image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 09/26/2011 for the course AMS 311 taught by Professor Tucker,a during the Spring '08 term at SUNY Stony Brook.

Page1 / 3

HW 7 - 30 E(X-Y)2 = E(X-Y)2]=E[cfw(X(Y)2]= E(X)2-2(X(Y(Y)2...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online